Maternal expression of miR-let-7d-3p and miR-451a during gestation influences the neuropsychomotor development of 90 days old babies: "Pregnancy care, healthy baby" study. (February 2023) - Nedel, Fernanda; Ferrúa, Camila P.; do Amaral, Cainá C.; Corrêa, Geovanna P.; Silveira, Roberta G.; Trettim, Jéssica P.; da Cunha, Gabriela K.; Klug, Adriana B.; Ardais, Ana Paula; Fogaça, Tatiane B.; Pinheiro, Karen A.T.; Bast, Rachel K.S.S.; et al.
Abstract: Introduction: Studies on maternal microRNA expression have emerged to better understand regulatory mechanisms during the gestational period, since microRNA expression has been associated with pregnancy disorders. Objectives: This study aims to investigate the association between the expression of the maternal microRNAs miR-let-7d-3p and miR-451a during the second gestational trimester and neuropsychomotor development at 90 days of life of infants. Methods: This is a case-control study nested within a cohort, with the groups being divided into dyads in which pregnant women presented Major Depressive Episode (MDE) (n = 64), these being the cases, and their respective controls (no MDE; n = 64). The Bayley Scale III was used to assess the outcome of child development, and MDE was assessed through the Mini International Neuropsychiatric Interview Plus. The analysis of miR-let-7d-3p and miR-451a was done via serum from the pregnant women, utilizing the qRT-PCR (n = 128). Results: The results indicated a negative association between expression levels of miR-451a (β −3.3 CI95% −6.4;-0.3) and a positive associated of the miR-let-7d-3p with the cognitive development domain (β 1.7 CI95% 0.1; 3.0), and a positive association between expression of miR-let-7d-3p with motor development of the infants (β 1.6 CI95% 0.3; 2.9). Conclusion: This is a pioneering study on the topic that indicates a biological interrelationship between the miRNAs miR-let-7d-3p and miR-451a evaluated during the pregnancy and the motor and cognitive domains of infant development at 90 days postpartum. Graphical abstract: Image 1 Highlights: The expression of maternal miR-let-7d-3p and miR-451a is associated with child development. Negative association between maternal expression of miR-451a and child cognitive development. Positive association between maternal expression of miR-let-7d-3p and child cognitive. Positive association between maternal expression of miR-let-7d-3p and child motor development. There is a biological interrelationship between the evaluated miRNAs and child development.